Fetal alcohol spectrum disorders and assessment of maxillary and mandibular arc measurements. Issue 7 (2nd June 2016) - Abell, Katherine; May, Warren; May, Philip A.; Kalberg, Wendy; Hoyme, H. Eugene; Robinson, Luther K.; Manning, Melanie; Jones, Kenneth Lyons; Abdul‐Rahman, Omar
Abstract : Fetal alcohol spectrum disorders (FASD) comprise a range of physical differences and neurologic deficits from prenatal alcohol exposure. Previous studies suggest that relative maxillary growth deficiency can accompany FASD. Using the Fetal Alcohol Syndrome Epidemiologic Research (FASER) database, we investigated how maxillary and mandibular arcs and the ratio between them differ between FASD and non‐FASD individuals. First, we established normative values for maxillary and mandibular arcs and maxillary‐to‐mandibular arc ratio. In our control group (545 males, 436 females), mean maxillary and mandibular arcs for males/females were 24.98/24.52 cm and 25.91/25.35 cm, respectively. The ratio was 0.9643 and 0.9676 for males and females, respectively. We then evaluated the effect of microcephaly, short stature, and low weight (<10th centile), individually on arcs in controls. Generally, arcs were reduced significantly but the ratio did not differ. We compared our controls to 138 male and 135 female FASD cases. We noted a significant difference in arcs in male and female groups, but not the ratio. We compared non‐FAS controls with reduced growth parameters to similar cases with FASD. We did not find a significant difference in arc or ratio measurements. Therefore, we conclude the effect of prenatal alcohol exposure on maxillary and mandibular arc measurements is primarily on overall facial growth and less on asymmetric growth of the maxilla relative to the mandible, at least using this technique. © 2016 Wiley Periodicals, Inc.